Age Features of Aggressive Behavior (Eurasian Medical Research Periodical, 2022)
Aggression and aggressive behavior in modern life are almost one of the most important problems discussed in the world. In modern science, various aspects of the phenomenon of aggression have been studied and described, but the problem has been and remains very important - a number of issues have not yet been developed